OPEN HEART SURGERY IN HEMODIALYSIS PATIENTS - YAMADA, Takafumi; MIYAGAWA, Naotaka; KUGIMIYA, Toshiyasu; TAKAGI, Masatake (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 1998)
We have made a study on perioperative management for open heart surgery in hemodialysis patients. Subjects were eight patients on hemodialysis for chronic renal failure who underwent open heart surgery at Nagasaki University Hospital between 1988 and 1996. Although there was no operative death among them, two hospital death occurred (each at 34 and 54 postoperative days) with various complications which were unrelated to either renal failure or hemodialysis trouble. As far as adequate hemodynamic state could be maintained, we tried to keep their water balance to dry side in the immediate preoperative period. In most instances, intraoperative hemodialysis could be avoided by correcting water and electrolyte balance properly by active hemodialysis, and by positive use of hemofiltration and removal enough of the infused cardioplegic solution during cardiopulmonary bypass. In the postoperative period, early introduction of continuous hemodiafiltration was useful for controlling water and electrolyte balance, and preventing metabolic acidosis and azotemia. Meticulous perioperative management under full understanding of peculiar pathophysiology of hemodialysis patients is essential to obtain satisfactory result of open heart surgery in these patients.